Virtue epistemology : essays on epistemic virtue and responsibility - Fairweather, Abrol; Zagzebski, Linda Trinkaus, 1946- (Oxford University Press, 2001)
American and British philosophers have broken new ground in exploring how the nature of knowledge can be normative. Virtue Epistemology is a new movement receiving the bulk of attention from top epistemologists and ethicists; this volume reflects the best work in that vein.